Analysis of User Perceptions on Interactive Learning Platforms Based on Artificial Intelligence - Eirene Sana; Anandha Fitriani; Purwanti; Djoko Soetarno; Maulana Yusuf (Pandawan Sejahtera Indonesia, 2024)
Education is one field that is increasingly adopting artificial intelligence (AI) technology in an effort to improve the learning experience. AI-based interactive learning platforms have become a significant trend in modern education. This research aims to analyze user perceptions of AI-based interactive learning platforms and identify factors that influence their acceptance of this technology. We conducted an analysis using the SmartPLS method to explore the relationship between variables that influence user perceptions of AI in education. Research data was collected through surveys given to educational participants using AI-based learning platforms. The results of this research include findings about the extent to which factors such as interaction quality, usability, and social factors influence user perceptions of AI-based learning platforms. The results of data analysis will provide valuable insight into how the educational community accepts and adopts AI technology in the learning process. It is hoped that this research will make a significant contribution to the understanding of the acceptance of AI technology in educational contexts, as well as provide guidance for the development of more effective interactive learning platforms. The findings of this research can also support decision making in implementing AI in educational settings.